2014
DOI: 10.2337/dc14-0210
|View full text |Cite
|
Sign up to set email alerts
|

Basal Insulin Peglispro Demonstrates Preferential Hepatic Versus Peripheral Action Relative to Insulin Glargine in Healthy Subjects

Abstract: OBJECTIVEWe evaluated the endogenous glucose production (EGP) and glucose disposal rate (GDR) over a range of doses of basal insulin peglispro (BIL) and insulin glargine in healthy subjects. RESEARCH DESIGN AND METHODSThis was a single-center, randomized, open-label, four-period, incomplete-block, crossover study conducted in eight healthy male subjects. Subjects had 8-h euglycemic clamps performed with primed, continuous infusions of BIL (5.1 to 74.1 mU/min) in three dosing periods and insulin glargine (20 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 31 publications
(20 reference statements)
5
72
0
Order By: Relevance
“…Also of note, a recent study in healthy subjects demonstrated preferential hepatic versus peripheral action of a novel, large basal insulin analogue (insulin peglispro) compared with insulin glargine. Initial results suggest that this insulin is also weight‐sparing 67. This provides further evidence that hepatoselectivity may indeed be an important mechanism contributing to the weight‐sparing effect of insulin detemir.…”
Section: Hepatoselective Hypothesismentioning
confidence: 83%
“…Also of note, a recent study in healthy subjects demonstrated preferential hepatic versus peripheral action of a novel, large basal insulin analogue (insulin peglispro) compared with insulin glargine. Initial results suggest that this insulin is also weight‐sparing 67. This provides further evidence that hepatoselectivity may indeed be an important mechanism contributing to the weight‐sparing effect of insulin detemir.…”
Section: Hepatoselective Hypothesismentioning
confidence: 83%
“…PegLispro achieves a statistically significantly greater improvement in glycemic control than insulin glargine, and the risk of nocturnal hypoglycemia is reduced by nearly half compared with insulin glargine (1,3,4,15,20,21,43,51). However, daytime hypoglycemic events were significantly increased, possibly due to its hepato-preferential action resulting in a greater inhibition of hepatic glucose output postprandially (20,49). It remains to be seen whether a reduction in the dose of short-acting insulin or other hypoglycemic agents may abolish this untoward daytime hypoglycemia risk.…”
Section: Arguments Challenging the Benefit Of The New Long-acting Insmentioning
confidence: 99%
“…There is also a lesser variability in glucose lowering with PegLispro compared with insulin glargine (56) accompanied by less weight gain and fewer nocturnal hypoglycemic episodes in early phase 2 studies with PegLispro in both type 1 (51) and type 2 diabetes (21,50,56). Its preferential hepatic (inhibition of glucose production) versus peripheral (glucose disposal) activity makes it perhaps more similar to endogenous insulin when compared with other exogenously administered insulins that possess a predominant effect on peripheral glucose disposal (1,3,4,15,20,21,49). In a series of phase 3 studies (IMAGINE), it shows a consistent, although marginal, but statistically greater HbA 1c -lowering capacity (0.2-0.3% HbA 1c ) than glargine U100 in persons with either type 1 or type 2 diabetes on intensified insulin therapy or persons with type 2 diabetes on basal insulin in addition to oral therapy (20,51,52).…”
Section: Arguments In Favor Of the New Insulinsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the phase I study, LY2605541 showed flat PK and PD profiles accompanied by glucose normalization, prandial insulin dose reduction, and no severe hypoglycemia [7]. In addition to the long and flat PK/PD profile, LY2605541 demonstrates preferential hepatic versus peripheral action relative to insulin glargine in healthy individuals [8]. In this euglycemic clamps study, insulin glargine resulted in increased glucose disposal rate (GDR) at insulin concentrations where endogenous glucose production (EGP) was significantly suppressed.…”
mentioning
confidence: 99%